How do you solve -2x + 2( 2x + 2) = 162x+2(2x+2)=16?

1 Answer
Apr 1, 2018

x =6x=6

Explanation:

So, first using the distributive property, you distribute the 22 to (2x+4)(2x+4). You get 4x+44x+4. Next, you add the -2x2x and the 4x4x to get 2x2x. After you subtract the 44 from the 1616 (You have to subtract, not add 44 because you are moving it across the equal sign. This means you have to use the opposite operation to cancel the 44. Thus, you subtract 44 to both ends). Your final equation should be 2x=122x=12. Lastly, you divide 22 to both sides, getting x=6x=6.